Gender Equality in Nigeria’s Private Sector : A Gender Gap Assessment of the 30 Most Capitalized Companies Listed on the Nigerian Exchange - International Finance Corporation (Washington, DC, 2022)
Nigeria is the largest economy in Africa, and it is projected to have the fifth largest population in the world by 2026. The gender gap is particularly acute in Nigeria, and three market failures stand out: (1) a persistent gender gap at the company leadership level; (2) lack of access to finance for women who want to start a business; and (3) women’s limited access to markets through supply chains and procurement opportunities. The International Finance Corporation (IFC) and Nigerian Exchange Limited (NGX) have joined forces to rally some of the largest Nigerian companies to increase women’s participation in private sector development. Through the Nigeria2Equal initiative, IFC is working with the chief executive officers (CEOs) of companies listed on NGX that are committed to implementing gender-smart solutions to reduce gender gaps across leadership, employment, and entrepreneurship. Through the Nigeria2Equal initiative, IFC is working with the chief executive officers (CEOs) of companies listed on NGX that are committed to implementing gender-smart solutions to reduce gender gaps across leadership, employment, and entrepreneurship. By conducting market research and publishing studies such as this report, IFC is establishing the business case for the private sector to invest in women in Nigeria, and are helping companies to identify gaps and constraints, and invest in reducing those gaps.